Corrosion Mechanism of Press-Hardened Steel with Aluminum-Silicon Coating in Controlled Atmospheric Conditions - Nikola Macháčková; Darja Rudomilova; Tomáš Prošek; Thierry Sturel; Maxime Brossard (Metals)
The effect of various atmospheric parameters on the corrosion mechanism of press-hardened steel (PHS) coated with Al-Si (AS) was studied. Quantitative models of the composition of soluble and stable corrosion products were developed. A high chloride concentration led to a localized corrosion due to the presence of cracks in the coating. Increased corrosion resistance of silicon-rich Al8Fe2Si and AlFe at the expense of the Al5Fe2 phase with low silicon content was shown. Under low-chloride-deposition conditions, the coating exhibited good corrosion resistance and provided sufficient protection to the underlying steel. The formation of more local anodes and cathodes under conditions of lower relative humidity led to a reduction in the depth of corrosion pits in the steel substrate. Constant high relative humidity and sulphate deposits on the surface were critical for the acceleration of steel corrosion in coating cracks.